Behavioral Factors in the National Quality Indicators through Implementing Total Quality Management - Wigati, Putri Asmita; Fatmasari, Eka Yunila; Suryawati, Chriswardhani; Arti, Dwi Windu Kinanti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: For 3 years running, there has been a difficulty in reaching the target of National Quality Indicators on the behavior of hand hygiene and the use of personal protective equipment by doctors, young dentists, and nurses from July to September 2022. This study aimed to describe employee behavior in achieving National Quality Indicators through the implementation of Total Quality Management (TQM) at Unimus Teaching Hospital of Dental and Oral in Semarang, Indonesia.Method: This cross-sectional study collected data from 75 employees of Unimus Teaching Hospital of Dental and Oral by accidental sampling technique. The instrument was developed by a structured questionnaire and analyzed using frequency distribution.Result: 11 National Quality Indicators have reached the target except the indicators of behavior of doctors during visiting hours (69%). The implementation of the Quality of the 10 aspects has been well implemented to support it, with the most implemented being the factors of scientific approach (96%), customer focus (94.7%), team work (94.7%), and long-term commitment (94.7%). Additionally, it is necessary to improve the aspects of competence human resources, education and training, passion with quality, and continuous system improvement to ensure the achievement of National Quality Indicators. The implementation of TQM is good. In supporting the achievement of National Quality Indicators, the hospital emphasizes more on education and training efforts, and in the aspect of structure, increasing the number and competence of its employees.